2006
DOI: 10.1007/s00424-006-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-synaptic block of neuromuscular transmission, muscle unloading and mechanical ventilation on skeletal muscle protein and mRNA expression

Abstract: To analyse mechanisms of muscle wasting in intensive care unit patients, we developed an experimental model where rats were pharmacologically paralysed by post-synaptic block of neuromuscular transmission (NMB) and mechanically ventilated for 9+/-2 days. Specific interest was focused on the effects on protein and mRNA expression of sarcomeric proteins, i.e., myosin heavy chain (MyHC), actin, myosin-binding protein C (MyBP-C) and myosin-binding protein H (MyBP-H) in fast- and slow-twitch limb, respiratory and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
49
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 56 publications
(59 reference statements)
16
49
0
Order By: Relevance
“…The results from this study and a previous study focusing on myofibrillar protein and mRNA expression (32) have documented the usefulness of this model for future and more detailed studies of muscle wasting in ICU patients. The model enables time-resolved studies, as well as studies regarding mechanical ventilation, neuromuscular blockade, muscle unloading, and corticosteroid treatment separately and in different combinations.…”
Section: Experimental Set-upsupporting
confidence: 57%
See 2 more Smart Citations
“…The results from this study and a previous study focusing on myofibrillar protein and mRNA expression (32) have documented the usefulness of this model for future and more detailed studies of muscle wasting in ICU patients. The model enables time-resolved studies, as well as studies regarding mechanical ventilation, neuromuscular blockade, muscle unloading, and corticosteroid treatment separately and in different combinations.…”
Section: Experimental Set-upsupporting
confidence: 57%
“…We observed a general downregulation of all these transcripts, except for myosin-binding protein H, indicating that the muscle wasting in the ICU is associated with a decreased protein synthesis (32). In addition to the lowered levels of TRα1, which has a role in myosin isoform switching (above), we have also identified NFATc1 as a potential mediator of the reduced transcription.…”
Section: Pathways In Protein Synthesismentioning
confidence: 62%
See 1 more Smart Citation
“…Although the exact underlying mechanisms for the diaphragm weakness are not known, these findings may point towards an altered quality of acto-myosin interactions in the affected diaphragm where also the loading pattern would be changed during ICU management (133,511,517,518). Interestingly, in intercostal muscles, there is a similar decline in myosin-to-actin ratio as in the limb muscle (512). Thus it may be speculated that the passive loading of the diaphragm by the mechanical ventilator (72 times/min in the rat model) had an impact on transcriptional regulation of myofibrillar protein synthesis but not on the activation of protein degradation pathways.…”
Section: Rodent Icu Modelmentioning
confidence: 98%
“…A central issue is whether denervation of muscle mimics the effects of unloading muscle caused by neuromuscular blocking agents in patients. A recent study compared muscle treated with denervation alone to muscle treated with the combination of neuromuscular blockade and corticosteroids and found differences (42). We have previously found that the addition of corticosteroids to denervation has profound effects on muscle (47,48), which suggests the differences were likely due to treatment with corticosteroids rather than difference between denervation and neuromuscular block.…”
mentioning
confidence: 92%